(untitled) (International Journal of Environmental Sciences, 2025)
To evaluate and map the spatial distribution of available manganese in agricultural soils of Basrah Province in southern Iraq using geospatial technologies, two regions were selected in the northern and southern of Basrah, with respective areas of 34,561.50 and 4,086.58 hectares respectively. A total of 36 representative samples were collected from each study region, synchronized with the satellite imagery acquisition of Landsat 8 for October 2023. Laboratory analyses were performed, and the correlation between available manganese and selected soil properties was assessed. In the northern region, available manganese content fell within the medium range across the entire area (100%), ranging from 8.93 to 15.80 mg kg⁻¹. In the southern region, 63% of the area showed manganese deficiency, 30% had low levels, and only 7% exhibited medium levels ranging from 0.12 to 10.83 mg kg-1. These findings indicated that the studied soils require and respond well to manganese fertilization. A significant negative correlation (r = -0.354) was observed between available manganese and total carbonate content in the southern region.